Effectiveness of Ambulatory Telemedicine Care in Older Adults: A Systematic Review - Batsis, John A.; DiMilia, Peter R.; Seo, Lillian M.; Fortuna, Karen L.; Kennedy, Meaghan A.; Blunt, Heather B.; Bagley, Pamela J.; Brooks, Jessica; Brooks, Emma; Kim, Soo Yeon; Masutani, Rebecca K.; Bruce, Martha L.; et al. (Journal of the American Geriatrics Society (JAGS), 2019)
BACKGROUND Disparities in healthcare access and delivery, caused by transportation and health workforce difficulties, negatively impact individuals living in rural areas. These challenges are especially prominent in older adults. DESIGN We systematically evaluated the feasibility, acceptability, and effectiveness in providing telemedicine (TMed), searching the English‐language literature for studies (January 2012 to July 2018) in the following databases: Medline (PubMed); Cochrane Library (Wiley); Web of Science; CINAHL; EMBASE (Ovid); and PsycINFO (EBSCO). PARTICIPANTS Older adults (mean age = 65 years or older, and none were younger than 60 years). INTERVENTIONS Interventions consisted of live, synchronous, two‐way videoconferencing communication in nonhospital settings. All medical interventions were included. MEASUREMENTS Quality assessment, using the Cochrane Collaboration's Risk‐of‐Bias Tool, was applied on all included articles, including a qualitative summary of all articles. RESULTS Of 6616 citations, we reviewed the full text of 1173 articles, excluding 1047 that did not meet criteria. Of the 17 randomized controlled trials, the United States was the country with the most trials (6 [35%]), with cohort sizes ranging from 3 to 844 (median = 35) participants. Risk of bias among included studies varied from low to high. Our qualitative analysis suggests that TMed can improve health outcomes in older adults and that it could be used in this population. CONCLUSIONS TMed is feasible and acceptable in delivering care to older adults. Research should focus on well‐designed randomized trials to overcome the high degree of bias observed in our synthesis. Clinicians should consider using TMed in routine practice to overcome barriers of distance and access to care. J Am Geriatr Soc 67:1737–1749, 2019